Effect of reducing ultraprocessed food consumption on obesity among US children and adolescents aged 7–18 years: evidence from a simulation model. Issue 2 (7th July 2021) - Livingston, Anne Scott; Cudhea, Frederick; Wang, Lu; Steele, Euridice Martinez; Du, Mengxi; Wang, Y Claire; Pomeranz, Jennifer; Mozaffarian, Dariush; Zhang, Fang Fang
Abstract : Background: Children and adolescents in the USA consume large amounts of daily calories from ultraprocessed foods (UPFs). Recent evidence links UPF consumption to increased body fat in youth. We aimed to estimate the potential impact of reducing UPF consumption on childhood obesity rate in the USA. Methods: We developed a microsimulation model to project the effect of reducing UPF consumption in children's diet on reducing the prevalence of overweight or obesity among US youth. The model incorporated nationally representative data on body mass index (BMI) percentile and dietary intake of 5804 children and adolescents aged 7–18 years from the National Health and Nutrition Examination Survey 2011–2016, and the effect of reducing UPF consumption on calorie intake from a recent randomised controlled trial. Uncertainties of model inputs were incorporated using probabilistic sensitivity analysis with 1000 simulations. Results: Reducing UPFs in children's diet was estimated to result in a median of −2.09 kg/m 2 (95% uncertainty interval −3.21 to –0.80) reduction in BMI among children and adolescents aged 7–18 years. The median prevalence of overweight (BMI percentile ≥85th) and obesity (BMI percentile ≥95th percentile) was reduced from 37.0% (35.9%, 38.1%) to 20.9% (15.1%, 29.9%) and from 20.1% (19.2%, 21.0%) to 11.0% (7.86%, 15.8%), respectively. Larger BMI and weight reductions were seen among boys than girls, adolescents than children, non-Hispanic black and Hispanic youth than non-Hispanic white youth, and those with lower levels of parental education and family income. Conclusions: Reducing UPF consumption in children's diet has the potential to substantially reduce childhood obesity rate among children and adolescents in the USA.